2021
DOI: 10.1038/s41398-021-01762-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential brain ADRA2A and ADRA2C gene expression and epigenetic regulation in schizophrenia. Effect of antipsychotic drug treatment

Abstract: Postsynaptic α2A-adrenoceptor density is enhanced in the dorsolateral prefrontal cortex (DLPFC) of antipsychotic-treated schizophrenia subjects. This alteration might be due to transcriptional activation, and could be regulated by epigenetic mechanisms such as histone posttranslational modifications (PTMs). The aim of this study was to evaluate ADRA2A and ADRA2C gene expression (codifying for α2-adrenoceptor subtypes), and permissive and repressive histone PTMs at gene promoter regions in the DLPFC of subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 70 publications
2
10
0
Order By: Relevance
“…We then examined the elements that may regulate the differential expression of the ADRA2A and some immune response genes identified in the study. A recent study on subjects with schizophrenia characterized that a promoter region in ADRA2A, epigenetically modified by both H3K4me3 and H3K27me3, could modulate the expression of ADRA2A in the dorsolateral prefrontal cortex [85]. Consistently, this study found that ADRA2A was highly expressed in the LM layer, and H3K4me3 was significantly enriched in its proximal promoter (≤1 kb).…”
Section: Discussionsupporting
confidence: 67%
“…We then examined the elements that may regulate the differential expression of the ADRA2A and some immune response genes identified in the study. A recent study on subjects with schizophrenia characterized that a promoter region in ADRA2A, epigenetically modified by both H3K4me3 and H3K27me3, could modulate the expression of ADRA2A in the dorsolateral prefrontal cortex [85]. Consistently, this study found that ADRA2A was highly expressed in the LM layer, and H3K4me3 was significantly enriched in its proximal promoter (≤1 kb).…”
Section: Discussionsupporting
confidence: 67%
“…For example, there is a link between insulin resistance and cognitive impairment 58 . In this regard, the hub genes of FTD-related modules including HEPB2 59 , CAMK1G 60 , ADRA2G 61 , C22orf132 62 are associated with cognitive impairment. Increasing evidence points to closely relevant between insulin signaling impairment and pathologic mechanisms of cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…A mouse knockout model showed increased startle reflex and aggression 27 . Differential gene expression 28 and genetic alterations 29 in ADRA2C also suggest a role in schizophrenia. DRD2 and DRD3 binding were associated with mammary and menstruation-related ADRs in SIDER 3032 .…”
Section: Resultsmentioning
confidence: 99%